Acetic acid stress in budding yeast: From molecular mechanisms to applications. Issue 7 (27th May 2021) - Guaragnella, Nicoletta; Bettiga, Maurizio
Abstract:  Acetic acid stress represents a frequent challenge to counteract for yeast cells under several environmental conditions and industrial bioprocesses. The molecular mechanisms underlying its response have been mostly elucidated in the budding yeast Saccharomyces cerevisiae, where acetic acid can be either a physiological substrate or a stressor. This review will focus on acetic acid stress and its response in the context of cellular transport, pH homeostasis, metabolism and stress‐signalling pathways. This information has been integrated with the results obtained by multi‐omics, synthetic biology and metabolic engineering approaches aimed to identify major cellular players involved in acetic acid tolerance. In the production of biofuels and renewable chemicals from lignocellulosic biomass, the improvement of acetic acid tolerance is a key factor. In this view, how this knowledge could be used to contribute to the development and competitiveness of yeast cell factories for sustainable applications will be also discussed. Take Away: Acetic acid stress is a frequent challenge for budding yeast. Signalling pathways dissection and system‐wide approaches reveal a complex picture. Cell fitness and adaptation under acid stress conditions is environment dependent. Tolerance to acetic acid is a key factor in yeast‐based industrial biotechnology. There is no 'magic bullet': An integrated approach is advantageous to develop performing yeast cell factories. Abstract : Multiple factors influenced acetic acid stress and tolerance in the budding yeast Saccharomyces cerevisiae .